KESIAPAN SUMBER DAYA DALAM IMPLEMENTASI KEBIJAKAN MANAJEMEN TALENTA DI LINGKUNGAN PEMERINTAH PROVINSI JAWA TENGAH - Dinda Farras Haniya; Amni Zakarsyi R.; Retna Hanani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
The authority to implement talent management within the Central Java Provincial Government is given to the BKD of Central Java Province. They as implementers have their own way of carrying out all stages of talent management. One important factor that needs to be prepared in the implementation of talent management, which can be seen from existing resources, such as funding, human resources and facilities. This study aims to analyze the readiness of resources in the implementation of talent management policies in the Central Java Provincial Government. This research method is a descriptive qualitative. The results of this study are that the Central Java Provincial BKD has been able to accommodate all the needs of talent management in terms of funding, so there are no problems with funding. In addition, based on the quality of human resources, BKD Central Java Province is able to apply the principles of good governance and merit in implementing talent management. Meanwhile, in terms of the quantity of human resources, BKD Central Java Province still lacks personnel to carry out talent management. Finally, when viewed from a facility standpoint, the Central Java BKD already has adequate facilities, especially regarding information systems. The information system is an important facility that needs to be continuously developed so that it can support Central Java Province BKD Employees in implementing talent management. Suggestions from this research is to add more assessors to meet the needs of talent management. In addition, BKD Central Java has to develop their information system so that the implementation of talent management policies is running effectively and efficiently.